MOTIVATION AND QUALITY OF LIFE AMONG PATIENTS WITH CHRONIC RENAL FAILURE UNDERGOING HEMODIALYSIS IN MEDAN, INDONESIA - Deddy Sepadha Putra Sagala; Jenny Marlindawani Purba; Nunung Febriyani Sitepu (Alta Dharma Publisher, 2019)
The increasing number of patient with chronic renal failure can also increase the number of patients undergoing hemodialysis. Hemodialysis is normally undergone by the patients to maintain their life as well as to transform their lifestyle. Hence, patients need effective motivation that will affect the quality of life of patients undergoing hemodialysis. This study aimed to analyze the correlation between motivation with quality of life in patients undergoing hemodialysis. It was a correlational study using a cross-sectional approach. This study was conducted at a private hospital in Medan. The research sample was all patients with chronic renal failure undergoing hemodialysis at Imelda Pekerja Indonesia Hospital in the year 2018, with the total number of sample was 79. The data was collected through questionnaire administration. Spearman test was performed to examine the data. The result of the study showed that there was a positive correlation between motivation and quality of life among patients with chronic renal failure undergoing hemodialysis (r=0.813; p<0.05). The high motivation of patients influences their quality of life to undergo hemodialysis. This study can be used as a reference for nurses to provide health education to patients and their families. High motivation and how to improve quality of life are essential course for the patients. Keywords: Motivation, Quality of Life, Chronic Renal Failure